Participación social en la gestión ambiental: estudio de caso en una unidad de conservación urbana en el municipio de São Paulo, Brasil - Cerati, Tania Maria; Queiroz de Souza, Aline (El Colegio de México A.C., 2016)
This article describes an immersion in the social reality of the community of the State Park of Fuentes de Ipiranga, an urban conservation unit in the city of São Paulo, the third largest remnant of the Atlantic Forest in the municipality. The case study presented here describes the participatory management process that included the groups interested in the action: the municipal authorities (prefecture of the city of Diadema), the state authorities (Institute of Botany) and the local community. In the field of research and action, focus group techniques were used to identify the main environmental conflicts in the area; interviews were conducted with residents to understand their perception of environmental issues, and regular meetings were held to plan the actions to be taken. The results indicate that there was a process of training citizens with regard to the organization of collective action, which yielded significant results that improved the social and environmental quality of the area.